2023
DOI: 10.3390/gels9060477
|View full text |Cite
|
Sign up to set email alerts
|

Developing Biomimetic Hydrogels of the Arterial Wall as a Prothrombotic Substrate for In Vitro Human Thrombosis Models

Abstract: Current in vitro thrombosis models utilise simplistic 2D surfaces coated with purified components of the subendothelial matrix. The lack of a realistic humanised model has led to greater study of thrombus formation in in vivo tests in animals. Here we aimed to develop 3D hydrogel-based replicas of the medial and adventitial layers of the human artery to produce a surface that can optimally support thrombus formation under physiological flow conditions. These tissue-engineered medial- (TEML) and adventitial-lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The prothrombin time measurements of the M1- and foam cell-containing hydrogels demonstrate that they are both capable of triggering blood coagulation. To investigate whether this activity could be due to enhanced tissue factor in the foam cells in the 3D neointimal biomimetic hydrogel, we used a previously developed microplate assay of extrinsic clotting factor activity [ 24 ]. This assay involves incubating the constructs with a solution containing inactive Factor VII (the target of tissue factor), and a fluorescent indicator of activated factor VII (FVIIa) activity, SN-17a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prothrombin time measurements of the M1- and foam cell-containing hydrogels demonstrate that they are both capable of triggering blood coagulation. To investigate whether this activity could be due to enhanced tissue factor in the foam cells in the 3D neointimal biomimetic hydrogel, we used a previously developed microplate assay of extrinsic clotting factor activity [ 24 ]. This assay involves incubating the constructs with a solution containing inactive Factor VII (the target of tissue factor), and a fluorescent indicator of activated factor VII (FVIIa) activity, SN-17a.…”
Section: Resultsmentioning
confidence: 99%
“…When digested by FVIIa, SN-17a becomes more fluorescent, and so the rate of fluorescence increase can be used to assess the tissue factor activity contained within each construct in the absence of any endogenously produced FVIIa. Previous experiments on samples containing human coronary artery smooth muscle cells have demonstrated that this fluorescence increase is dependent upon both the presence of a tissue factor-bearing construct and the presence of inactive Factor VII, demonstrating that the fluorescence increases are due to the presence of tissue factor in the sample [ 24 ]. However, previous studies have demonstrated that macrophages in atherosclerotic plaques are also able to produce FVII [ 45 ], indicating that fluorescent increases will be sensitive to the total activity of the extrinsic clotting factors, tissue factor, and factor VIIa, within this sample ( Figure 6 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances towards more vessel like in-vitro models have now progressed beyond the inclusion of endothelial cells to vascular constructs in an attempt to include other vascular components and avoid the use of rigid chambers which are much stiffer than the vascular wall [ 58 ▪▪ ]. To achieve this, bioprinting has been adopted.…”
Section: Other Vascular Components and Arterial Constructsmentioning
confidence: 99%